Unilateral Basal Ganglia Hyperdensity in a Previously Undiagnosed Diabetic Patient Presenting with Hemichorea-Hemiballism (Hchb) - Bhattarai, Manoj (Journal of Nobel Medical College, 2016)
Non-ketotic hyperglycemia induced hemichorea-hemiballism (HCHB) is a rare condition with characteristic neuroimaging findings in a diabetic patient. This paper reports a 61-year-old male previously undiagnosed diabetic patient presenting with HCHB as the first presentation of diabetes.Journal of Nobel Medical CollegeVolume 5, Number 1, Issue 8, January-July 2016, 66-68